The Microcomputer—Its Applicability to Special Education. - Taber, Florence M. (Focus on Exceptional Children, 1981)
The article provides a brief history of the microcomputer and discusses how it is used in regular and special education. The computer was first used in the classroom in the 1960's, but multiple-choice questions simply appeared on the screen. Microcomputer can assist the educator in individualizing instruction, providing a nonthreatening presentation to the learner, and simplifying record keeping and other administrative duties. In creating or purchasing software, one must be aware of what language the computer understands. Three major consideration in purchasing hardware includes technical, training and software.